Diet Quality and Risk of Parkinson Disease: A Prospective Study and a Meta-Analysis. (29th May 2020) - Liu, Yi-Hsuan; Jensen, Gordon; Na, Muzi; Mitchell, Diane; Wood, G Craig; Still, Christopher; Gao, Xiang
Abstract: Objectives: Several dietary components have been shown to be neuroprotective against risk of neurodegeneration. We thus examined the associations between diet quality and risk of Parkinson disease (PD) in a prospective cohort study and a meta-analysis. Methods: Included in the cohort study were 3653 participants (1519 men and 2134 women; mean age: 81.5 years) in the Geisinger Rural Aging Study longitudinal cohort in Pennsylvania. Diet quality was assessed using a validated dietary screening tool containing 25 food- and behavior-specific questions in 2009 (baseline). Potential PD cases were identified using electronic health records based on ICD10 code (G20) and PD-related treatments. Incident PD cases were defined as being diagnosed after 1 year of follow-up and receiving PD-related medication treatments. Hazard ratios (HRs) and 95% confidence intervals (CIs) across diet quality tertiles were calculated using cox proportional hazards models after adjusting for age, sex, race, educational level, smoking, oral health, obesity and living arrangement. We further performed a meta-analysis by pooling our study with four published papers on this topic. Random-effects model was utilized to calculate the pooled risk ratios and 95% CIs. Results: During a mean of 6.94 years of follow-up, 47 incident PD cases were documented. Having high diet quality at baseline was associated with lower PD risk ( p -trend = 0.02). The adjusted HR was 0.39 (95% CI: 0.17–0.89) for the highest vs the lowest diet quality tertiles. The meta-analysis including 140, 617 individuals also showed that adherence to a healthy dietary pattern was associated with lower risk of incident PD (pooled risk ratio = 0.64; 95% CI: 0.49–0.83). Conclusions: Having high diet quality was associated with lower future risk of PD. Funding Sources: United States Department of Agriculture, Agricultural Research Service agreement.